Text messaging as a new method for injury registration in sports: A methodological study in elite female football - Nilstad, A.; Bahr, T.; Andersen, T. E. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Methodological differences in epidemiologic studies have led to significant discrepancies in injury incidences reported. The aim of this study was to evaluate text messaging as a new method for injury registration in elite female football players and to compare this method with routine medical staff registration. Twelve teams comprising 228 players prospectively recorded injuries and exposure through one competitive football season. Players reported individually by answering three text messages once a week. A designated member of the medical staff conducted concurrent registrations of injuries and exposure. Injuries and exposure were compared between medical staff registrations from nine teams and their 159 affiliated players. During the football season, a total of 232 time-loss injuries were recorded. Of these, 62% were captured through individual registration only, 10% by the medical staff only, and 28% were reported through both methods. The incidence of training injuries was 3.7 per 1000 player hours when calculated from individual registration vs 2.2 from medical staff registration [rate ratio (RR): 1.7, 1.2-2.4]. For match injuries, the corresponding incidences were 18.6 vs 5.4 (RR: 3.4, 2.4-4.9), respectively. There was moderate agreement for severity classifications in injury cases reported by both methods (kappa correlation coefficient: 0.48, confidence interval: 0.30-0.66).